The Potential of Marine Ecotourism in Pasumpahan Island Sungai Pisang Regency West Sumatera Province - Pajri Aris; Dessy Yoswaty; Mubarak Mubarak (Ilmu Perairan (Aquatic Science), 2021)
The aim of the study was to discover the potential level of pasumpahan island as destination for marine ecotourism. The method used was survey methods, data was consisting of primary and secondary data. Interviewing sampling method was used purposively, particularly for tourist sample for local Beach has a big potential in marine tourism and prossess a big chance to develop in marine ecotourism sector. It was showed by the suitability value of marine ecotourism development. The value was resulted through tourism proponent criteria, total scores of  IKW and SWOT analysis